Self-Checking Cell-Based Assays for GPCR Desensitization and Resensitization. (September 2014) - Fisher, Gregory W.; Fuhrman, Margaret H.; Adler, Sally A.; Szent-Gyorgyi, Christopher; Waggoner, Alan S.; Jarvik, Jonathan W.
G protein–coupled receptors (GPCRs) play stimulatory or modulatory roles in numerous physiological states and processes, including growth and development, vision, taste and olfaction, behavior and learning, emotion and mood, inflammation, and autonomic functions such as blood pressure, heart rate, and digestion. GPCRs constitute the largest protein superfamily in the human and are the largest target class for prescription drugs, yet most are poorly characterized, and of the more than 350 nonolfactory human GPCRs, over 100 are orphans for which no endogenous ligand has yet been convincingly identified. We here describe new live-cell assays that use recombinant GPCRs to quantify two general features of GPCR cell biology—receptor desensitization and resensitization. The assays employ a fluorogen-activating protein (FAP) reporter that reversibly complexes with either of two soluble organic molecules (fluorogens) whose fluorescence is strongly enhanced when complexed with the FAP. Both assays require no wash or cleanup steps and are readily performed in microwell plates, making them adaptable to high-throughput drug discovery applications.